Jiří Stanislav Guth-Jarkovský in the Interwar Olympic Movement - František Kolář (Jan Długosz University in Częstochowa, 2019)
The article follows the work of JiříStanislav Guth-Jarkovský in the given period both on the domestic and on the international scene. In the new Czechoslovak state, it was necessary to establish a new Czechoslovak Olympic Committee which would serve as a representative of athletes of all nationalities. This, however, proceeded very slowly. With the strengthening of the status of sports associations, their young officials also asked for a greater share of COC's decision-making. There-fore, in the second half of the 1920s, there was a crisis in the Czechoslovak Olympic Movement, to which Guth-Jarkovsky responded by retreating. Throughout the interwar period, however, he re-mained an active member of the International Olympic Committee. At first, he was the Secretary General, later a member of its executive board. He actively participated in the design and adoption of the Olympic Charter and organization of the 8thOlympic Congress in Prague in 1925. However, in 1936 his reputation was damaged by his support of the XI. Olympic Games in Nazi-dominated Berlin.